18FDG-PET/CT Specificity for the Detection of Lymphoma Recurrence in the Tonsils. Issue 4 (November 2021) - West, Jonathan D.; Kim, Mary E.; Lapalma, Dorian M.; Vergara-Lluri, Maria; Conti, Peter; Chambers, Tamara N.; Swanson, Mark S.
Objective: In patients with a history of lymphoma who demonstrate palatine tonsil uptake on posttreatment PET/CT (positron emission tomography/computed tomography), tonsillectomy is often performed to evaluate for lymphoma recurrence. However, predictive clinical and imaging factors for true tonsil recurrence in this setting are not well established; this will be explored herein. Study Design: Retrospective case series. Setting: Patients treated at a tertiary medical center from January 2008 to May 2020. Methods: Chart review was performed on all patients with a history of treated lymphoma in clinical remission who presented for evaluation of abnormal PET/CT imaging findings and subsequently underwent tonsillectomy. Results: Among 15 patients who met inclusion criteria, 14 had benign findings on surgical pathology, yielding a false-positive rate of 93%. The patient with malignancy was identified on biopsy after inconclusive surgical pathology and is the only documented case of recurrence in this specific patient population throughout the literature. The patient presented with B symptoms, irregularly shaped tonsils, increased lymph node activity on PET/CT, and uptrending bilateral tonsil activity but with one of the lowest maximum standardized uptake values of the cohort. The singular distinguishing feature for the patient with recurrent disease was a prior tonsil biopsy suspicious for recurrence, which prompted the otolaryngology referral. Conclusion: PET/CT lacks specificity in identifying lymphoma recurrence in the oropharynx. Clinical and radiographic features that were previously considered concerning for recurrence are most likely not indicative of malignancy in this patient population. Our findings call into question whether tonsillectomy should be routinely performed in this patient population.